Revision of Austrosignum Hodgson and Munnogonium George & Strömberg (Paramunnidae) with descriptions of eight new genera and two new species, (Crustacea: Isopoda: Asellota) - Just, Jean; Wilson, George D.f. (Zootaxa, 2007)
The paramunnid genera Austrosignum Hodgson, 1910 (type species A. glaciale Hodgson, 1910) and Munnogonium George & Strömberg, 1968 (type species M. waldronense George & Strömberg, 1968) are re-diagnosed. Twenty seven species are reviewed. Austrosignum is restricted to two described species, Munnogonium to five described species. The remaining 20 species are placed in the following eight new genera: Boreosignum (type species Austrosignum maltinii Schiecke & Fresi, 1972), Cryosignum (type species Paramunna lunata Hale, 1937), Meridiosignum (type species M. macquariensis sp. nov.), Tethygonium (type species T. quadricuspis sp. nov.), Quetzogonium (type species Austrosignum dentatum Winkler, 1994), Advenogonium (type species Austrosignum fuegiae Doti & Roccatagliata, 2005), Zizzygonium (type species Paramunna magellanensis Winkler, 1994), Kussakinella (type species Austrosignum spinosum Kussakin, 1982).